A morte(in)visível: o significado da morte encefálica entre profissionais da saúde do serviço público municipal de Santos - Cordeiro, Roseane Carlos [UNIFESP] (2015)
The study aimed to seek to understand the meaning of brain death among health professionals of the municipal public service of Santos, on the subject of death (in) visible.